Creating entrepreneurial ecosystems for the reindustrialization of the Russian economy: the crisis impulse of 2020 - Yurchenko Konstantin (E3S Web of Conferences, 2020)
The global economy, which has been successfully developing for a long time under the influence of the globalization trend, experienced a serious external shock in 2020. The sharp halt in growth and the fall in GDP in most countries have led to the need to develop mechanisms for restoring growth, which are based on consumer and business activity. Russia has been hit by a double whammy of the crisis, as in addition to the decline in business activity, the impact of a decrease in demand for export commodities, while at the same time falling prices for them, affects. The article, based on fundamental and empirical works devoted to the study of business ecosystems and behaviors of a resource-dependent economies, the author, using techniques of statistical analysis substantiates opened for countries to undertake in the medium term reindustrialization of the economy, forming with the updated effective entrepreneurial ecosystem.